Placental mesenchymal dysplasia - Gujral, Kanwal; Dimri, Nandita; Bhalla, Sunita; Mansukhani, Chandra; Nayar, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Placental Mesenchymal Dysplasia (PMD) is a rarely encountered placental lesion often associated with high fetal mortality and morbidity. We report here a case of PMD with a favourable outcome. The salient features of diagnosis, management and literature review are discussed.